PENGARUH CORPORATE ENVIRONMENTAL PERFORMANCE DAN ENVIRONMENTAL COST TERHADAP CORPORATE VALUE DENGAN FINANCIAL PERFORMANCE SEBAGAI VARIABEL INTERVENING (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2022-202 - Novita Efirawandefit; Yuliusman; Nela Safelia (Jurusan Akuntansi FEB Universitas Jambi, 2025)
Environmental damage caused by mining activities has increased attention to environmental performance and costs. This study aims to analyze the effect of Corporate Environmental Performance and Environmental Cost on Corporate Value, with Financial Performance as an Intervening Variable, in mining companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. The data analysis method used in this study is Partial Least Square – Structural Equation Modeling (PLS-SEM) run using SmartPLS4 software. Based on the analysis results, only Corporate Environmental Performance has a positive and significant effect on Corporate Value. Environmental Cost and Financial Performance do not significantly influence Corporate Value. Financial Performance is unable to mediate the relationship between Corporate Environmental Performance and Environmental Cost on Corporate Value. These results confirm that the Indonesian capital market values environmental commitment as a signal of legitimacy and reputation, but the financial benefits of environmental expenditures are not visible in the short term. Companies need to make environmental management a sustainable strategy to strengthen long-term value.